Persepsi Mahasiswa tentang Humor Seksis sebagai Bentuk Kekerasan Seksual secara Verbal - Kusuma Diah Tantri; Martini Martini; Nova Scorviana (Institut Nalanda, 2024)
The rise of sexist humor, which is a form of verbal sexual violence, is one of the important things that needs to be studied. Students as figures who will have an important role in society need to have a proper understanding of forms of sexual violence, such as sexist humor. Therefore, it is important in the end to know how students perceive sexist humor as a form of verbal sexual violence. This research uses a descriptive method with a qualitative approach. Data collection techniques were carried out by observation, interview, documentation, and literature study. The subjects in this study were 5 students who are currently actively studying in higher education who were determined using purposive sampling technique. The results showed that there are two main perceptions of sexist humor, namely sexist humor as a form of verbal sexual violence and sexist humor as a form of joke. The researcher also found that the determination of perceptions was motivated by gender factors and the closeness between the perpetrator and the victim.